The Impact of Covid-19 lockdown on Intention to Follow Preventive Measures in Vietnam: Integrated Protection Motivation Theory and Theory Planed Behavior - Duc Trung Nguyen; Van Dat Tran; Abdul Ghafoor (Cogent Business & Management, 2022)
Coronavirus (COVID-19), a highly transmissible disease that poses a global danger to human populations from 2019, had a pandemic breakout in Vietnam in May 2021. A total of 311 people responded to the online survey, which had 29 questions. The causal linkages of the latent factors construct were determined using structural equation modeling (SEM). Moreover, it integrated Protection Motivation Theory (PMT) and extended Theory of Planned Behavior (TPB) to evaluate factors affecting the intention to follow of COVID-19 prevention measures. As a consequence, SEM revealed that understanding of COVID-19 has a direct impact on risk perception. Moreover, the perceived risk of COVID-19 also had significant impacts on people's attitude and perceived behavior control. While this study discovered a positive influence of attitude and perceived behavioral control on subjective norms. Intention to follow had been significant direct effects by subjective norm, perceived risk. Thus, the current study is one of the first studies to analyze factors affecting the intention to follow COVID-19 prevention measures during the global pandemic. This study also contributes to the managers and operators of measures to prevent the spread of diseases to find appropriate methods based on the factors affecting the effectiveness of COVID-19 prevention approaches.
Keywords: 650; attitude; intention to follow; perceived behavioral control; perceived risk of Covid-19; subjective norm